Assessment of Pelvic Floor Dysfunction Following Vaginal Versus Abdominal Hysterectomy: A Longitudinal Study - Sohaila Ameen, Uzma Aziz, Sadia Dilawar, Lubna Malik, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hysterectomy is one of the most frequently performed gynecological procedures worldwide. Objective: To evaluate and compare the frequency and severity of pelvic floor dysfunction following vaginal and abdominal hysterectomy in women operated for benign uterine conditions. Methodology: This comparative cross-sectional study was conducted at Sir Ganga Ram Hospital, Lahore from January 2023 to June 2023. A total of 205 women aged 30–60 years who had undergone hysterectomy for benign indications were included. Participants were divided into two groups: Group A (vaginal hysterectomy, n = 102) and Group B (abdominal hysterectomy, n = 103). Data were collected using a structured questionnaire, including the Pelvic Floor Distress Inventory (PFDI-20), Urogenital Distress Inventory (UDI-6), and Pelvic Organ Prolapse Quantification (POP-Q) system. Results: The mean age of participants was 46.2 ± 7.9 years, and the groups were comparable in baseline characteristics. Urinary incontinence was significantly more frequent in the abdominal hysterectomy group (28.1%) compared to the vaginal group (15.7%) (p = 0.03). Vaginal vault prolapse was more common following vaginal hysterectomy (19.6%) than abdominal hysterectomy (9.7%) (p = 0.04). The mean total PFDI-20 score was significantly higher among women who underwent abdominal hysterectomy (42.7 ± 11.4) compared to those with vaginal hysterectomy (36.3 ± 10.9) (p = 0.01). Sexual dysfunction and bowel symptoms were slightly more common in the abdominal group but were not statistically significant. The mean hospital stay was shorter in the vaginal hysterectomy group (3.4 ± 1.1 days) than in the abdominal group (6.1 ± 2.3 days) (p < 0.001). Conclusion: It is concluded that vaginal hysterectomy is associated with better postoperative pelvic floor outcomes, fewer urinary symptoms, and quicker recovery compared to abdominal hysterectomy. Keywords: Hysterectomy, Vaginal hysterectomy, Abdominal hysterectomy, Pelvic floor dysfunction, Urinary incontinence